2014
DOI: 10.1186/1687-5281-2014-8
|View full text |Cite
|
Sign up to set email alerts
|

Soft computing-based colour quantisation

Abstract: Soft computing techniques have shown much potential in a variety of computer vision and image analysis tasks. In this paper, an overview of recent soft computing approaches to the colour quantisation problem is presented. Colour quantisation is a common image processing technique to reduce the number of distinct colours in an image. Those selected colours form a colour palette, while the resulting image quality is directly determined by the choice of colours in the palette. The use of generic optimisation tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…1 , namely Lenna, Peppers, Mandrill, Sailboat, Airplane, and Pool. In all experiments, the number of colours in the palette is set to 16 [ 8 ] and we set , , K (the number of clusters during grouping) to 5, , , and . HMS is run with a population size of 50 for 500 iterations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 , namely Lenna, Peppers, Mandrill, Sailboat, Airplane, and Pool. In all experiments, the number of colours in the palette is set to 16 [ 8 ] and we set , , K (the number of clusters during grouping) to 5, , , and . HMS is run with a population size of 50 for 500 iterations.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the octree and Neuquant algorithms outperform the popularity and median cut approaches. Furthermore, it is clear that the soft computing-based colour quantisation algorithms outperform octree and Neuquant confirming that methods based on soft computing techniques are effective tools for colour quantisation [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process involves separating zeros from nonzero data, as shown in Figure-3.The zero-array can be computed easily by calculating the number of zeros between two nonzero data. For example, assume the following AC-Matrix=[0.5, 0, 0, 0, 7.3, 0, 0, 0, 0, 0, -7], the zero-array will be [0, 3,0,5,0] where the zeros in red refer to nonzero data existing at these positions in the original AC-Matrix and the numbers in black refer to the number of zeros between two consecutive non-zero data. In order to increase the compression ratio, the number "5" in the zeroarray can be broken up into "3" and "2"zeros to increase the probability (i.e.…”
Section: Two Level Discrete Cosine Transform (Dct)mentioning
confidence: 99%
“…Pixels associated with a certain area, commonly described based on features such as colour or texture, exhibit more commonalities than those assigned to different areas. Image segmentation is employed in a variety of applications, such as satellite image analysis [1,2], colour quantisation [3], tumour detection [4], food quality evaluation [5], and modelling of microstructures [6], to name a few.…”
Section: Introductionmentioning
confidence: 99%